Emergence of ESBL-Producing Klebsiella oxytoca in Bovine Mastitic Milk: A Study in Gujarat, India - I Prajapati, Bhavesh; P Katira, Bhavin; Deep Singh, Ratn; M Solanki, Kiran; R Bariya, Akshay; J Patel, Kelvina (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
The present study reports first detection of extended spectrum β-lactamase (ESBL) producing Klebsiella oxytoca, an opportunistic pathogen, from bovine milk samples collected from milk-shed regions of Gujarat. The study included a total of 270 bovine milk samples comprising of 175 fresh milk sample from apparently healthy dairy animals and 95 mastitic milk samples. A total of five K. Oxytoca isolates were identified based on results of cultural, biochemical and molecular techniques, all from mastitic milk samples only, yielding an overall prevalence of 5.26 % (5/95). None of the milk sample from healthy animals was found positive for the presence of Klebsiella oxytoca. Phenotypic characterization revealed that 80 % (4/5) isolates were ESBL producing Klebsiella oxytoca based on both results of Combination Disc Diffusion test (CDDT) and HiCrome ESBL agar culture. Further, ESBL producing genes, viz., blaTEM and blaSHV were found in one and four isolates, respectively, whereas virulent gene wabG was found in all five isolates. None of the K. Oxytoca isolates was found positive for the presence of ESBL producing gene blaCTX-M-1, and virulent gene kfuBC.